Faktor-Faktor Yang Mempengaruhi Perusahaan Manufaktur Terdaftar Di Bei Melakukan Voluntary Auditor Switching - nugroho teguh benianto; Hana Puji Lestari (AKUNTANSI DEWANTARA, 2021)
Auditor’s Independence issue is the main cause why companies must do auditor switching mandatorily. Many questions rise when actually there were some companies did voluntary auditor switching outside the rule of auditor switching KMK No. 359/KMK.06/2003 which has been revised to be PMK No. 17/PMK.01/2008. This research is purposed to find empirical evidences about the factors that influence manufacturing companies which are listed in BEI to do voluntary auditor switching. Variables that are used in this research are going concern opinion (OGC), management changes (PM), auditor’s reputation (RA), financial distress (KK), auditor’s fee (LNFEE), and voluntary auditor switching (SWITCH).The data being used is from manufacturing company which is listed in BEI in 2007-2010 period. Data collecting method which used in this research is method purposive sampling, that based on criteria which has been determined before. Based on the method purposive sampling, research sample total is 276 companies. Hypothesis in this research are tested by logistic regression analytical method.Result of this research indicates that variable having which significantly effect the voluntary auditor switching is auditor reputation. On the other hand,other variables like going concern opinion, management changes, financial distress, and auditor’s fee do not have significant effect on company decision to do voluntary auditor switching.